(3GdeLehYI GdCOHjIs - (3eLehYI ef GdeDdajfs ((3GdbSWfWjfjI s)
(3ChdgG (B:s
(3ef cJGH JMaI GdYQhS ddYdGeI TgGH GdOjf CMeO GdJLGfi Qhi SajGf GdKhQi Cf Ydi Hf CHj WGdH cQe Gddg hLgg cGf cKjQkG eG jJeKd Hbhd GdTGYQ JZfi GddPGPI eef fGd TghJg ef GdMQGe hjHbi GdCKe hGdYGQ s
(3BNQgG (B:s
(3EfeG TQa GdEfSGf Ydi LejY GdMjhGf HGdfWb hGdage aEf ScJ hde jage YGO HgjekG gPG BNQ eG LeYJg ef GdMce GdjhfGfjI hGdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs